2016
DOI: 10.1208/s12249-016-0617-9
|View full text |Cite
|
Sign up to set email alerts
|

The Serum-Resistant Transfection Evaluation and Long-Term Stability of Gene Delivery Dry Powder Based on Mesoporous Silica Nanoparticles and Polyethyleneimine by Freezing-Drying

Abstract: Mesoporous silica nanoparticles (MSNs) with large surface area, tunable pore size, and low toxicity can act as suitable vehicles for drug and gene delivery. An MSN/DNA/PEI complex delivery system was prepared by using MSNs to hold plasmid DNA coated with polyethyleneimine (PEI), and the dry powder formulation was produced by freeze-drying with trehalose as lyoprotectant. The MSN/DNA/PEI complexes successfully enhanced the gene expression with about 1.5-fold higher efficiency as compared with the control, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In the last decade, different cationic polymers, such as polyethylenimine (PEI) [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) [ 74 , 75 ], chitosan derivatives [ 76 ], poly l -arginine [ 77 ] or poly l -lysine (PLL) [ 78 ], have been reported as coatings for silica nanoparticles in gene delivery systems, either through simple electrostatic interactions with the surface silanol groups, through covalent silane coupling with trialkoxysilanes, or by amidation reactions of amine-containing polymers with carboxylated NPs [ 20 ]. Table 3 summarizes a variety of different polymer-modified silica-based gene delivery formulations recently reported in literature.…”
Section: Hybrid Silica Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, different cationic polymers, such as polyethylenimine (PEI) [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) [ 74 , 75 ], chitosan derivatives [ 76 ], poly l -arginine [ 77 ] or poly l -lysine (PLL) [ 78 ], have been reported as coatings for silica nanoparticles in gene delivery systems, either through simple electrostatic interactions with the surface silanol groups, through covalent silane coupling with trialkoxysilanes, or by amidation reactions of amine-containing polymers with carboxylated NPs [ 20 ]. Table 3 summarizes a variety of different polymer-modified silica-based gene delivery formulations recently reported in literature.…”
Section: Hybrid Silica Nanoparticlesmentioning
confidence: 99%
“…Among the existing cationic polymers, PEI is the most commonly used and is generally accepted as the gold standard for nonviral gene delivery [ 15 , 64 ]. This polymer has a high density of amine groups which, not only enhance the electrostatic interaction with genetic material and the cellular uptake but also help to avoid the endo/lysosomal pathway degradation due to the “proton sponge effect” [ 64 , 69 ]. This process is characterized by the protonation of amine groups upon acidification in the endosome, leading to increased osmotic pressure and eventual swelling and burst of the endosome, consequently releasing the nanosystem into the cytoplasm [ 79 , 80 ].…”
Section: Hybrid Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-viral systems include (physical: naked DNA, DNA bombardment, electroporation, sonoporation, hydrodynamic, ultrasound, magnetofection, gene gun) and (chemical: cationic lipids, different cationic polymers, cligonucleotides, dendrimers, lipid polymers, inorganic nanoparticles, cell-penetrating peptides) and viral systems include retroviral, adenoviral, adeno association, helper-dependent adenoviral systems, hybrid adenoviral systems, herpes simplex virus, pox virus, lentivirus, epstein-barr virus, cis and trans-acting elements, replication-competent vectors, envelope protein pseudotyping of viral vectors [3,4]. Non-viral vector systems, based on cationic lipids, dendrimers, polymers and peptides have recently been favorable for gene delivery [5], because they are much safer than viral systems that are exposed to immunogenic or inflammatory responses. Viral vectors can achieve higher transduction efficiency and long-term expression of the gene, but they have fundamental problems, such as immunogenicity, insertional mutagenesis, tumorigenicity, capacity and the cost of producing in a large scale [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The PEI-coated MSN system has become so widespread among the scientific community that some studies have already been performed trying to evaluate different processing options, to enable long-term storage that ensure that the hybrid system maintains all of its properties and biological behavior. For example, Zhang et al reported that by incorporating the cryoprotectanttrehalose, PEI-coated MSNs could be lyophilized, maintaining their integrity for at least 4 months at room temperature, which would enable the mass production and distribution of this system for therapeutic application [ 84 ].…”
Section: Mesoporous Silica Nanoparticles For Gene Deliverymentioning
confidence: 99%